Fostering Sustainable Digital Leadership in Educational Organization, Systematic Literature Review using NVIVO and PRISMA - Giovanni, Netaniel; Ali, Hapzi; Nurhaida, Ida (Dinasti Publisher, 2024)
This research identifies the role of digital leadership in educational organizations. The analysis uses qualitative analysis. The research method used is SLR (Systematic Literature Review) with the PRISMA protocol through stages supported by the Publish or Perish and NVIVO applications. All supporting publications were searched through Publish or Perish and Dimension Database. The article search results found 543 related studies in 2020-2024, then filtered through the PRISMA protocol to 35 articles selected to answer the research questions. The results of the article are: 1) Sustainable digital leadership involves several essential aspects: agility, resilience, and adaptability. 2) There are 10 sustainable digital leadership competencies that digital leaders need to have: Focus on Vision, Repetitiveness, Communication and Collaboration, Flexibility, Resourcefulness, Risk-Taking and Recovery, Critical Thinking, Culture of Learning, Responsiveness, and Creativity and Innovation. 3) Future leaders must prioritize understanding digital change and assessing digital leadership competencies. This competency development can take the form of training, talent development, support from experts, and digital leadership assessments. 4) Essential to provide financial resources, infrastructure, work environment, and access to the latest learning technology. 5) The most vital aspect of digital leadership is how leaders collaborate and empower to realize the vision, implement change, and create a creative and innovative educational organizational environment.